La bicicleta de Sumji - Oz, Amos; Martínez-Lage, Miguel; Oz, Amos. (Madrid : Siruela, 2015)
A young boy in modern-day Jerusalem trades away one possession after another, only to find something much more wonderful, his first love.
Online resource; title from ePub title page (Digitalia, viewed April 21, 2017)
Keywords: Jerusalem -- Juvenile fiction; Electronic books